2017
DOI: 10.1088/1361-648x/aa5f26
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature superconductivity in one-unit-cell FeSe films

Abstract: Since the dramatic enhancement of the superconducting transition temperature (T ) was reported in a one-unit-cell FeSe film grown on a SrTiO substrate (1-UC FeSe/STO) by molecular beam epitaxy (MBE), related research on this system has become a new frontier in condensed matter physics. In this paper, we present a brief review on this rapidly developing field, mainly focusing on the superconducting properties of 1-UC FeSe/STO. Experimental evidence for high-temperature superconductivity in 1-UC FeSe/STO, includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 161 publications
4
69
0
1
Order By: Relevance
“…As for carrier doping, we demonstrated that the T c of FeSe was raised to 35 K by extremely high-density electron accumulation using electric-double layer transistor (EDLT) structures [13,14]. This kind of carrier-induced high T c has also been reported in [15−18] and observed for monolayer-thick FeSe [9,19].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…As for carrier doping, we demonstrated that the T c of FeSe was raised to 35 K by extremely high-density electron accumulation using electric-double layer transistor (EDLT) structures [13,14]. This kind of carrier-induced high T c has also been reported in [15−18] and observed for monolayer-thick FeSe [9,19].…”
Section: Introductionsupporting
confidence: 54%
“…According to the above XRF result, we then tried to tune the [Fe]/[S] ratio to reach stoichiometry by adding excess S to the PLD bulk targets. The nominal compositions of PLD targets we examined were 9 FeS 1+x (x = 0, 0.1, 0.2, and 0.4). Other parameters were all fixed; i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The 11 type iron-based superconductor (FeSe 1−x Te x ) have drawn much attention in basic research and applications, especially in superconducting mechanism exploration [1,2], because of their simplest crystal structure and non-toxic properties [3,4]. The bulk FeSe showed a superconducting transition temperature (T c ) of about 8K [5], and the superconductivity onset in α-FeSe was reported to attain a broad maximum of 37 K under 7 GPa hydrostatic pressure [6].…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Fore xample,g raphene films have much larger carrier mobilities on hexagonal boron nitride substrates than on silicon oxide substrates. [8] Forl ayered heterostructures, the structures of rock salt-like 2D layers have also been found to vary systematically with thickness and also with the dichalcogenide constituent that they are layered with in heterostructures. [8] Forl ayered heterostructures, the structures of rock salt-like 2D layers have also been found to vary systematically with thickness and also with the dichalcogenide constituent that they are layered with in heterostructures.…”
Section: Two-dimensionalmaterialsandtheirintegrationintovandermentioning
confidence: 99%